Jesus of Isaac of Troki; a Critical Presentation from the Perspective of Fundamental Theology - Skierkowski, Marek (Studia Teologiczne Białystok Drohiczyn Łomża, 2024)
This article regards Isaac Ben Abraham of Troki (c. 1533-1594 or c. 1525-1586), a Karaite scholar who wrote a famous apology entitled Hizuk Emunah. It remained for a long time in manuscript and each copyist could modify the text according his own views. The work was first published, in Latin translation, by Wagenseil in his Tela Ignea Satanae (1681), but it was an English translation (appeared in 1851) that gave the apology a permanent meaning in the field of understanding Jesus. This article deals critically with the English copy showing in what exactly consisting the main problem with Jewish reading of the four gospels.